Choosing to study music in high school: Teacher support, psychological needs satisfaction, and elective music intentions. (November 2019) - Freer, Elisabeth; Evans, Paul
High school students do not value music education highly, nor do they see it as a useful part of their academic pathways. When music becomes an elective subject, low enrolment in elective classes is seen as a challenge for music educators. This study aimed to further investigate this issue by examining the motivational climate of the music classroom, including the perceptions of the music teacher, in the development of student motivation for music. It also examined how these motivational factors influenced students' intentions to take music as an elective subject. A hypothesized model based on self-determination theory was tested using structural equation modeling (SEM), based on survey data from N = 395 students from 11 schools. The hypothesized model fit the data well. Students' basic psychological needs fulfillment was predicted by the perceived needs-supportive practices of their teachers. These in turn were predictive of students' elective intentions. Using multi-group SEM analyses, findings were invariant across gender, school type, year at school, and socio-economic status, and the role of prior music learning was examined. The results indicate that an effective target for increasing students' motivation and value for music at school may be the motivational climate of the music classroom.